(untitled) (Education in the 21st Century, 2023)
In the organization of professional education of the pedagogue it is presently important for the learner not only to form a complete system of theoretical content of the profession but also to integrate the learner’s creative potential and ensure the level of creative preparedness for providing alternative situational solutions. The development of professional power-based competences firstly focuses on the primary goals that guide professional education in a number of directions: independence, cognitive activeness, socialization, self-focused development. At the same time, the development of the specialist’s culturological and socio-pedagogical competences and skills in alternative ways is also given importance to, which, combined with the knowledge, will form the complete picture of knowledge, competences and skills of the future specialist. The goal of the current research is to reveal the applicable significance of art technologies in the formation of learners’ culturological and socio-pedagogical competences. Among primary objectives, it has been set to disclose the pedagogical possibilities of art technologies, to study the mechanisms of satisfying cultural needs of the learner and forms of emotional discharge, the verbal and non-verbal communication mechanisms by means of art, as well as to put forward the culturological and socio-pedagogical aspects of art technologies in the organization of the learner’s professional learning. Art technologies fulfill a number of functions: introspective-cathartical, corrective-regulating, communicative-reflective. Due to them, art technologies obtain synergic functionality, thus having a multidirectional impact on the subject, after which the socio-pedagogical activity is carried out. Based on the means of art, art technologies include elements of pedagogy, medicine, psychology, culturology, sociology and other fields, having deeper and vast influence on the subject. Its structural elements are as follows: a) subjects of influence, b) means of art, c) needs and motives, d) interinfluence and interaction, e) results. Art technologies have a health- and culture-based influence and they are necessary to everyone for individual development. As a human subjective experience, the emotional experience art technologies have, is manifested in three dimensions: internal experience (subjective perception), behavioral reaction (cry, laughter, shiver, shout, etc.), physiological processes (increase of blood pressure, sweating, vascular spasm, muscular tension, heartbeat). It is manifested in the communication model, which can be linear, interactive or transactional. Therefore, it is necessary to clearly understand the nature and content of art technologies, to combine them with the problem that concerns the child, to choose the type that will be useful for revealing, correcting the problem, or making it look acceptable. Based on this, art technologies are classified according to the principle of communicative forms of verbal and non-verbal art means, for example: non-verbal art technologies – painting therapy, color therapy, music therapy, paratherapy, sand therapy, etc.; and verbal art technologies – puppet therapy, drama therapy, theater therapy, fairy tale therapy, bibliotherapy, etc. Each of these works with the problem of the person in a different way, hence, from the socio-pedagogical point of view it is worth understanding to what extent the use of art technologies contributes to the formation of cultural and social competences in the socio-pedagogical activity. In the framework of the current research, we have thoroughly examined the types of art technologies often used in creative art therapy, their content and role in the formation of the learner’s socio-cultural competences. As a result, we have found out that in addition to professional primary competences, there is a need to also develop these competences in order to expand the scope of perceptual communication, humanization, as well as to provide a value-based direction to the socio-pedagogical process. Conclusion The investment of art technologies today is not sufficiently involved in the organization of pedagogical activities. There is a need to further promote it and to contribute not only to the learner’s academic knowledge, but also to their cultural, moral, and emotional growth. There is a need to ensure the development of learners’ ability to solve socio-pedagogical practical problems through the teacher-student communication with the help of art technologies. It is necessary to develop the ethics of aesthetic construction of social relations among learners. There is a necessity to make the infinite possibilities of art technologies available to the learner, which will serve as a basis for organizing poly-art education and a means of developing the child’s social and emotional intelligence.